Muslim dietitian-patient spiritual conversations and its’ challenges: a descriptive cross-sectional study - Afandi, Aflah; Mohamad, Hasbullah; Mohd. Abu Bakar, Wan Azdie; Mamat, Nik Mazlan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Spirituality is essential in patient care. In dietetics, the patient-centred care approach has a significant role in promoting caring relationships with the patients in dietary counselling. While integrating spirituality in clini cal practice influences patients’ ability to cope with illness, there is a paucity of research on spirituality in dietetics. This study aimed to discover the proportion of Muslim dietitians who inquired about patients’ spiritual needs and its association with socio-demographic factors, identify selected conversations on spiritual concern and its challenges. Method: This cross-sectional study adopted selected items from The International NERSH-Cohort questionnaire. A new semi-structured question on responses to patients’ spiritual concerns was also evaluated (4 items; alpha=.79). Data were gathered through an online survey and analysed using descriptive analysis and Pearson chi-square.Re sults: Out of ninety-eight respondents, only 3% reported always making an attempt to inquire about patients’ spiritual needs, whereas 44% had never made such an inquiry. The duration of practising dietetics was not associated with inquiring spiritual needs practices. When the Muslim patients brought up a discussion on spiritual concern, 38% of the Muslim dietitians had responded that only Allah has the power to heal and grant happiness. This study highlights that Muslim dietitians’ most common obstacles to addressing spiritual concerns during dietary counselling were the fear of offending the patients and insufficient knowledge/training. Conclusion: There are ways for Muslim dietitians to engage in spiritual conversations during dietary counselling, but the existing challenges indicate a calling for for mal training.